Upaya Mewujudkan Produktivitas Kerja Berdasarkan Jaminan Keselamatan dan Kesehatan Kerja yang Diterima Karyawan, Efisiensi Kerja dan Perilaku Inovatif - Arif Rachman Putra; Didit Darmawan (TIN: Terapan Informatika Nusantara, 2022)
Work productivity has become a key focus in an increasingly complex and changing business environment. The process of measuring and improving work productivity has become a pressing challenge for organizations in various sectors. This study explains the underlying issues of work productivity and the associated managerial implications. Analysis is conducted on factors that affect productivity, including occupational health and safety, work efficiency and innovative behavior. A quantitative approach was used in this study. The data collected came from a specially designed survey administered to employees. The number of employees who responded to the questionnaire was in accordance with the sample requirement, which was 130 employees from the production division only. These employees are employees of companies located in Sidoarjo City. The data that has been collected will then be analyzed using multiple linear regression analysis. Through SPSS version 26, the proof of data analysis can be seen. From the analysis that has been done, it can be concluded that occupational safety and health insurance and work efficiency and innovative behavior have a significant positive effect on work productivity. Occupational safety and health (K3) and work efficiency are the main pillars in creating a productive and sustainable work environment